Role of Financial Literacy, Risk Perception, and Investment Experience in Investment Decisions of Millenial and Z Generation in Jabodetabek - Asry, Shofia; Paulina, Julinta; Tarigan, Budi Akhmad; Siagian, Ade Onny (International Journal of Business, Law, and Education, 2024)
This study investigates the roles of financial literacy, risk perception, and investment experience in shaping investment decisions. Utilizing a sample of 500 individuals, we conducted descriptive statistics, reliability and validity testing, structural equation modeling (SEM), and moderation analysis to explore these relationships. The results reveal that higher financial literacy and investment experience are positively associated with better investment decisions, while higher risk perception is negatively associated with investment outcomes. Furthermore, financial literacy moderates the effect of risk perception, and investment experience enhances the positive impact of financial literacy on investment decisions. These findings underscore the importance of financial education and practical experience in fostering informed and strategic investment behavior. The study offers valuable insights for developing targeted educational programs and advisory services to enhance investor competence and confidence.